NiO–ZrO2 nanocomposite modified electrode for the sensitive and selective determination of efavirenz, an anti-HIV drug. Issue 50 (4th June 2015) - Thapliyal, Neeta; Osman, Nadir S. E.; Patel, Harun; Karpoormath, Rajshekhar; Goyal, Rajendra N.; Moyo, Thomas; Patel, Rajkumar
<x xml:space="preserve">Abstract</x> A highly sensitive NiO–ZrO2 nanocomposite modified electrode was fabricated for trace analysis of efavirenz in pharmaceutical and biological samples.